Adoption by Lesbians and Gay Men in Europe: Challenges and Barriers on the Journey to Adoption. Issue 2 (3rd April 2018) - Messina, Roberta; D'Amore, Salvatore
ABSTRACT: No psychological research has been done investigating the experiences of adoption by sexual minorities living in Europe. This qualitative study is the first cross-national research within the European context giving the floor to LG (lesbian and gay) adoptive parents in order to explore the main challenges they encountered in the transition to adoptive parenthood. Sixty-two LG adoptive parents (16 lesbians and 46 gay men) living in Belgium ( n = 14), France ( n = 26), and Spain ( n = 22) participated in this study. Semi-structured interviews were conducted in order to gather information about two key steps in the adoptive path: the decision making and the adoption process itself. Results revealed that while choosing to adopt, LG adoptive parents experienced numerous self-doubts and emotional conflicts driven by introjected heteronormative assumptions about family. During the adoption procedure, they were confronted with a large number of challenges and legal roadblocks connected to their sexual minority status. Exploring the experience of the first generation of LG adoptive parents in Europe provides insight into the great impact that the sociolegal context has on their lives. Findings suggest the necessity of promoting practice geared not only to fight discrimination but also to provide better support to LG people throughout the adoption process.